Luminescent properties of Tb3＋ doped high density borogermanate scintillating glasses - 钱珊 黄立辉 赵士龙 徐时清 (Journal of rare earths, 2017)
Tb3＋-doped high density borogermanate glasses were prepared by melt-quenching method. Their physical and luminescent properties including differential thermal analysis（DTA）, density, transmittance spectra, photoluminescence, and X-ray excited luminescence spectra were investigated. The densities of the glasses doped with Tb3＋ were in the range from 5.690 to 6.086 g/cm3. Under UV and X-ray excitations, the glasses showed intense green emissions. The lifetimes of Tb3＋ doped borogermanate glasses were in the range from 1.597 to 1.869 ms. The results indicated that Tb3＋ doped borogermanate glasses could be scintillator candidate used in X-ray detection application.